"Outdated Laws, Outspoken Whores": Exploring sex work in a criminalised setting. (May 2017) - Baratosy, Roxana; Wendt, Sarah
Abstract: This article explores the experiences of sex workers living and working in South Australia under laws that criminalise their profession. A qualitative research methodology was used to interview sex workers about their work experiences. It was found that working in a criminalised setting raised particular concerns for sex workers including an erosion of workplace protections, outreach services, access to health service and increased policing. This article argues that criminalising sex work leads to human rights violations, therefore sex work should be decriminalised to ensure workers are protected. The themes from the interviews build qualitative evidence supporting the decriminalisation of sex work. This research has been supported by the Sex Industry Network of South Australia (SIN).